TEACHING VOCABULARY THROUGH MIND MAPPING TECHNIQUE TO THE EIGHTH GRADE STUDENTS OF SMP SANTO THOMAS 3 MEDAN - Sirait, Lilia Junita; Pangaribuan, Jontra Jusat; Tarigan, Karisma E. (Kairos English Language Teaching Journal, 2020)
The aim of this study is to find whether Mind Mapping Technique works effectively on improving the eighth grade studentsâ€™ achievement in vocabulary and to know the studentsâ€™ responses after being taught by using Mind Mapping Technique. in order toÂ achieve the objectives of study, a classroom action research was designed and carried out in this study. The subjects of this study were 27 students of class VIII- 81 Â OF SMP Santo Thomas 3 Medan in academic year 2018/2019. Test, observation sheet, and field notes were used as a instruments for collecting data. The results of the study showed significant improvement of the studentsâ€™ vocabulary. It is proved by the studentsâ€™ mean score of each test: pre-test was 65,33%, formative test was 72,59% and post-testÂ was 85,92% . In addition, the, the analysis result of the observation sheet and field notes showed Mind Mapping Technique channge the studentsâ€™ learning behavior being better than before. They were more enthusiastic during the teaching learning process in each cycle. The analysis result of questionnaire showed that Mind Mapping TechniqueÂ was useful to most of students to improve their learnig interest in vocabulary. Based on the results of those study instruments, it can be concluded that Mind Mapping Technique as learning technique gives the improvement to studentsâ€™ vocabulary. It is recommended for English teacher to apply Mind Mapping Technique in teaching vocabulary in order to improve studentsâ€™ vocabulary.